"‘Cause It Has to Happen": Exploring Teachers’ Resistance to LGBT Literature and Issues in a Teacher Inquiry Group (LEARNing Landscapes, 2015)
This paper explores teachers’ resistance to LGBT literature and issues by examining how a group of teachers, as part of a social justice research project, responded to an article that examined reasons why teachers who hold anti-homophobic views still resist teaching LGBT texts and topics in their classrooms. Boler and Zembylas’s (2002) notion of a "pedagogy of discomfort" provides a framework for understanding reluctance to move out of one’s comfort zone. The story of how one of the research participants pushed the boundaries of possibility by undertaking subsequent professional development initiatives at her school offers an alternative to teacher resistance.
Keywords: LGBT; professional development; social justice; pedagogy of discomfort; teacher resistance